2015
DOI: 10.1039/c4ra15546g
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic lignin composite sorbent for chromium(vi) adsorption

Abstract: A novel magnetic lignin composite removes Cr(vi).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…This adsorbent showed a removal efficiency of 99.99% when the pH was 2 and the initial Cr(VI) concentration was 300 mg/l [97]. A similar study was conducted by using chitosan as the polymer instead of polypyrrole, and a removal efficiency of 98% was reported at pH 2 and initial Cr(VI) concentration of 200 mg/l [96]. A cross-linked silica gel/chitosan-g-poly(butyl acrylate) nanocomposite showed a maximum Cr(VI) adsorption capacity of 55.71 mg/g [131].…”
Section: Nanoadsorbents For Chromium Remediationmentioning
confidence: 66%
See 1 more Smart Citation
“…This adsorbent showed a removal efficiency of 99.99% when the pH was 2 and the initial Cr(VI) concentration was 300 mg/l [97]. A similar study was conducted by using chitosan as the polymer instead of polypyrrole, and a removal efficiency of 98% was reported at pH 2 and initial Cr(VI) concentration of 200 mg/l [96]. A cross-linked silica gel/chitosan-g-poly(butyl acrylate) nanocomposite showed a maximum Cr(VI) adsorption capacity of 55.71 mg/g [131].…”
Section: Nanoadsorbents For Chromium Remediationmentioning
confidence: 66%
“…As has been appropriately noted by Pan et al [17], more research needs to be focused on the immobilisation of Cr(III) obtained after reducing Cr(VI) by biofilms, as the insoluble Cr(III) can form organo-Cr(III) complexes, which become toxic for cells in high concentrations. Biosorption is an advantageous technique as it costs less, is highly effective, does not have any toxic side effects, the biosorbent can be rebuilt, and the adsorbed metal can be recovered for possible later usage [96].…”
Section: Conventional Processes For Chromium Remediationmentioning
confidence: 99%
“…Recently, Nair et al [14] investigated the chitosan-alkali lignin composites for adsorbing Cr (VI) and the result indicated that 95% of Cr (VI) ions could be removed under the given conditions. Similarly, Song et al [15] prepared a magnetic lignin composite for adsorption of Cr (VI). Recently, the waterresistant lignin/PVA blend fibers were also fabricated to remove Cr (VI) ions, and obtained an excellent absorbability of 350.87 mg/g, meanwhile presented the promising regeneration [16].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the source of chromium pollution in environment from waste water of coating industries, paint factory, ink factory, tanneries, oil refineries, textile mills, and also from ore refining process. Many research have been done to prevent and reduce chromium(VI) content in water such as using bark seed powder to adsorb chromium(VI) in batch and coloumn method [2], and using moringa seed as biofloculant to reduce chromium(VI) level [3], and adsorption using chitosan-alumina [4], chitosan-modified 1,3,5-tribenzoic acid [5], activated carbon [6], metal organic framework (MOF) [7], magnetic lignin [8], chitosan nanoparticle [9], multiwalled carbon nanotube [10], mesoporous magnetic nanosphere [11], hydroxyapatite-cellulose composite [12], mesoporous carbon microsphere [13], Fe-montmorillonite [14], and agricultural biomass [15].…”
Section: Introductionmentioning
confidence: 99%